Effect of Application of Sunflower and Coconut Oils Over the Skin of Low Birth Weight Babies in Prevention of Nosocomial Infection - Das, Shishir Ranjan; Rahman, AKM Matiur; Chowdhury, AKM Azad; Hoq, Md. Mahbubul; Deb, Sudip Ranjan (Journal of Dhaka Medical College, 2013)
J Dhaka Medical College, Vol. 21, No. 2, October, 2012, Page 160-165 DOI: http://dx.doi.org/10.3329/jdmc.v21i2.15339